Survey of the Actual Practices Used for Endoscopic Removal of Colon Polyps in Korea: A Comparison with the Current Guidelines - Jeongseok Kim; Tae-Geun Gweon; Min Seob Kwak; Su Young Kim; Seong Jung Kim; Hyun Gun Kim; Sung Noh Hong; Eun Sun Kim; Chang Mo Moon; Dae Seong Myung; Dong-Hoon Baek; Shin Ju Oh; et al. (Gut and Liver)
Background/Aims: We investigated the clinical practice patterns of Korean endoscopists for the endoscopic resection of colorectal polyps. Methods: From September to November 2021, an online survey was conducted regarding the preferred resection methods for colorectal polyps, and responses were compared with the international guidelines. Results: Among 246 respondents, those with <4 years, 4-9 years, and ≥10 years of experience in colonoscopy practices accounted for 25.6%, 34.1%, and 40.2% of endoscopists, respectively. The most preferred resection methods for non-pedunculated lesions were cold forceps polypectomy for ≤3 mm lesions (81.7%), cold snare polypectomy for 4-5 mm (61.0%) and 6-9 mm (43.5%) lesions, hot endoscopic mucosal resection (EMR) for 10-19 mm lesions (72.0%), precut EMR for 20-25 mm lesions (22.0%), and endoscopic submucosal dissection (ESD) for ≥26 mm lesions (29.3%). Hot EMR was favored for pedunculated lesions with a head size <20 mm and stalk size <10 mm (75.6%) and for those with a head size ≥20 mm or stalk size ≥10 mm (58.5%). For suspected superficial and deep submucosal lesions measuring 10-19 mm and ≥20 mm, ESD (26.0% and 38.6%) and surgery (36.6% and 46.3%) were preferred, respectively. The adherence rate to the guidelines ranged from 11.2% to 96.9%, depending on the size, shape, and histology of the lesions. Conclusions: Adherence to the guidelines for endoscopic resection techniques varied depending on the characteristics of colorectal polyps. Thus, an individualized approach is required to increase adherence to the guidelines.